Munda make over series 2: Zambia - The Mediae Company; Chilambe, Pedro Anglaze; Gamoyo, Majambo Jarumani; Koech, Grace Jerotich; Ghosh, Aniruddha; Girvetz, Evan Hartunian (2023)
Knowledge is the most powerful in the hands of those who can put it into practice. This is the driving philosophy of Munda Makeover, a weekly TV broadcast conceptualized together by The Mediae Company with the CGIAR in Zambia that visits family farms to demonstrate improved agricultural practices and help communities thrive in a changing climate.